Acute haemodynamic and metabolic effects of felodipine in congestive heart failure. Issue 4 (April 1984) - Timmis, A D; Campbell, S; Monaghan, M J; Walker, L; Jewitt, D E
Abstract : Felodipine is a new calcium antagonist with a high degree of vascular selectivity. To examine its potential value as an afterload reducing agent in congestive heart failure 11 patients were studied. Substantial increments in cardiac index were associated with a fall in systemic vascular resistance. Left ventricular end diastolic pressure was also significantly reduced. Although left ventricular maximum dP/dt remained unchanged, maximum dP/dt/P increased. Left ventricular unloading was reflected by a reduction in cavity dimensions and a shift in the relation between end systolic pressure and dimension downwards and to the left. The myocardial oxygen supply to demand ratio was also improved: coronary sinus flow increased significantly despite a decline in myocardial oxygen consumption. These beneficial haemodynamic and metabolic effects suggest that felodipine may extend the clinical application of calcium antagonists to include the treatment of congestive heart failure.